2012
DOI: 10.1080/07370016.2012.645721
|View full text |Cite
|
Sign up to set email alerts
|

Using the Omaha System as a Framework to Demonstrate the Value of Nurse Managed Wellness Center Services for Vulnerable Populations

Abstract: Nurse managed wellness centers (NMWCs) are academic service settings where baccalaureate nursing students gain rich community health clinical experience while providing valuable wellness services to a vulnerable population. The Omaha System provides a framework for generating meaningful data that is essential for describing the value of NMWCs. A retrospective study of Omaha System assessments from 9 NMWCs provides descriptive data about the characteristics of the patient population and patient outcomes in rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 19 publications
3
20
0
Order By: Relevance
“…Seven studies using NOC used the NOC rating to measure changes in the condition of patients from admission to discharge (Azzolin et al, 2013;da Silva et al, 2015;Park, 2013;Scherb, Stevens, & Busman, 2007;Scherb et al, 2011;Schneider, Barkauskas, & Keenan, 2008;Tseng & Moorhead, 2014). One study used the Omaha system (Thompson, Monsen, Wanamaker, Augustyniak, & Thompson, 2012). One study used the Omaha system (Thompson, Monsen, Wanamaker, Augustyniak, & Thompson, 2012).…”
Section: Enable Evaluation Of Nursing-sensitive Outcome Indicatorsmentioning
confidence: 99%
See 4 more Smart Citations
“…Seven studies using NOC used the NOC rating to measure changes in the condition of patients from admission to discharge (Azzolin et al, 2013;da Silva et al, 2015;Park, 2013;Scherb, Stevens, & Busman, 2007;Scherb et al, 2011;Schneider, Barkauskas, & Keenan, 2008;Tseng & Moorhead, 2014). One study used the Omaha system (Thompson, Monsen, Wanamaker, Augustyniak, & Thompson, 2012). One study used the Omaha system (Thompson, Monsen, Wanamaker, Augustyniak, & Thompson, 2012).…”
Section: Enable Evaluation Of Nursing-sensitive Outcome Indicatorsmentioning
confidence: 99%
“…A similar result was noted by Park (2013) regarding patients with heart failure. Thompson et al (2012) used the Omaha system to describe patients at a nurse-managed wellness center as well as patients' health problems and whether their health improved. Azzolin et al (2013) noted that eight interventions from NIC showed significant improvement according to the outcome score for patients with heart failure in the indicators functional status, self-care, and symptom control.…”
Section: Enable Evaluation Of Nursing-sensitive Outcome Indicatorsmentioning
confidence: 99%
See 3 more Smart Citations